2022
DOI: 10.3389/fpls.2022.932912
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming With Melatonin Promotes Seed Germination and Seedling Growth of Triticale hexaploide L. Under PEG-6000 Induced Drought Stress

Abstract: Melatonin (N-acetyl-5-methoxytryptamine, MT) can mitigate abotic stress, including drought stress on a number of crops. However, it is unclear whether and how seed priming with melatonin alleviates the effects of drought stress on seed germination and seedling growth of triticale (Triticale hexaploide L.). In this study, we investigated the effects of seed priming with MT on seed germination, protective enzyme activity, superoxide anion, and hydrogen peroxide in triticale under PEG-6000 induced drought stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
4
13
0
Order By: Relevance
“…The results show that the highest germination rate was found in GA 3 2 and BR4 hormones and chitosan2 osmotic priming treatments. The possible explanation for these increases is that GA and BR hormones are growth-promoting hormones involved in seed germination and inhibiting the water uptake accompanying embryonic growth ( Aziz and Pekşen, 2020 ; Heshmati et al., 2021 ; Guo et al., 2022 ). The vigor index is the percentage of viable seeds, and vigor testing assesses the seed’s capacity to grow healthy seedlings under less-than-ideal or challenging conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that the highest germination rate was found in GA 3 2 and BR4 hormones and chitosan2 osmotic priming treatments. The possible explanation for these increases is that GA and BR hormones are growth-promoting hormones involved in seed germination and inhibiting the water uptake accompanying embryonic growth ( Aziz and Pekşen, 2020 ; Heshmati et al., 2021 ; Guo et al., 2022 ). The vigor index is the percentage of viable seeds, and vigor testing assesses the seed’s capacity to grow healthy seedlings under less-than-ideal or challenging conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal seed priming treatment concentration was screened out according to the germination dynamics and seedling growth status. Germination potential (GP), germination rate (GR), and vigor index (VI) were recorded through equation 1, equation 2, and equation 3 respectively ( Guo et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed not only SAM lack of phytotoxicity, but also stimulation of seeds germination percentage. Positive role of various metabolites was shown also in other seed germination experiments e.g., priming of triticale ( Triticale hexaploide L.) seeds with melatonin resulted in increased germination rate by 57.67% [ 66 ]. In other experiments it was shown that treatment of seeds with gibberellic acid and/or Indole Acetic Acid (IAA) improved germination parameters and subsequent cultivation of Masson pine ( Pinus massoniana ) and Aspilia Africana [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 91%
“…MEL treatment resulted in higher SG rate and germination index due to higher germination potential and elevated levels of total polyunsaturated FAs, and double bond index under DS 106,107 . MEL priming improved SG by increasing AO activity and reducing ROS production and malonaldehyde contents in seeds under polyethylene glycol‐6000 (PEG6000) induced DS 108 . Moreover, osmo‐priming with MEL enhances seed hydration which subsequently increases hydrolysis of reserve materials, thus improves SG 109 …”
Section: Mel Sg and Abiotic Stressorsmentioning
confidence: 99%